2018
DOI: 10.1504/ijrapidm.2018.10010809
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of H13 tooling element with conformal cooling channel using MIG cladding

Abstract: Visit www.inderscience.com for details of over 380 titles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It was found that the only situation where cracking could be avoided was to apply a pre-heating and a post-weld annealing. Legesse et al [30] used a hybrid CMT-milling approach to manufacture an AISI H13 die. It was found that the workpiece could be manufactured avoiding cracks by using a pre-heating system.…”
Section: Test Casementioning
confidence: 99%
“…It was found that the only situation where cracking could be avoided was to apply a pre-heating and a post-weld annealing. Legesse et al [30] used a hybrid CMT-milling approach to manufacture an AISI H13 die. It was found that the workpiece could be manufactured avoiding cracks by using a pre-heating system.…”
Section: Test Casementioning
confidence: 99%
“…Hybrid additive/subtractive manufacturing [35][36][37]: This combines the best of both worlds but can be complex to implement and control. It may also require specialized equipment, which increases the overall cost.…”
mentioning
confidence: 99%